A non-metallic porphyrin / graphene oxide nanocomposite and an electrochemical sensor made thereof

By conducting π-π non-covalent interactions between THPP and graphene oxide, the GO/THPP composite material was synthesized, the glassy carbon electrode was modified, and an electrochemical sensor with a wide linear range was constructed, which solved the Cu2+ and Pb2+ detection selectivity in the existing technology. and poor reproducibility, achieving high sensitivity and selectivity detection, low detection limit and good anti-interference performance.

CN116678925BActive Publication Date: 2025-01-21肖礼全
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310421051.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-19
Publication Date
2025-01-21
Estimated Expiration
2043-04-19

AI Technical Summary

Technical Problem

The prior art is difficult to achieve high sensitivity and selective detection of Cu2+ and Pb2+, and traditional electrodes are susceptible to dirt during detection, resulting in overlapping voltammetry responses, poor selectivity and repeatability.

Method used

By conducting π-π non-covalent interactions between 5,10,15,20-tetrahydroxyphenyl-21H,23H-porphyrin (THPP) and graphene oxide (GO), an electronic material with strong electron transfer ability and electrochemical properties was synthesized. GO/THPP composite material with excellent chemical properties is used to modify glassy carbon electrodes to construct electrochemical sensors with a wide linear range.

Benefits of technology

It achieves highly sensitive and selective detection of Cu2+ and Pb2+, with detection limits of 1.5μM and 1.6μM respectively. It has the characteristics of good anti-interference, wide detection range, good reproducibility and stability, and can successfully achieve actual water quality. Simultaneous determination of Cu2+ and Pb2+ remaining in the sample.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116678925B_ABST
    Figure CN116678925B_ABST
Patent Text Reader

Abstract

The present invention relates to a non-metallic porphyrin graphene oxide nanocomposite and an electrochemical sensor made thereof, belonging to the technical field of electrochemical detection. The present invention modifies THPP on the surface of GO through π-π non-covalent bond interaction without destroying the sheet structure of GO. After the two are combined, the wrinkles on the surface of GO become relatively flat, and the layers overlap each other, which greatly improves the conductivity and chemical stability of the composite material. The synergistic effect between GO and THPP accelerates the electron transfer between the redox probe and the electrode surface. Secondly, the electrochemical sensor prepared by the present invention is effective for Cu 2+ and Pb 2+ The detection limits of the samples were 1.5μM and 1.6μM, respectively. + 、Co 2+ NH 4+ 、Na + Mg 2+ 、Al 3+ 、Zn 2+ , Ca 2+ 、SO4 2‑ 、NO3 ‑ 、S2O8 2‑ , Cl ‑ It has good anti-interference in water samples, and has the characteristics of wide detection range, good reproducibility and stability, and can successfully realize the residual Cu in actual water samples. 2+ and Pb 2+ simultaneous determination.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a non-metallic porphyrin oxide graphene nanocomposite and an electrochemical sensor made thereof, belonging to the technical field of electrochemical detection. Background Art

[0002] Heavy metal ions and their compounds are ubiquitous in the natural environment. In recent years, heavy metal pollution has attracted widespread attention. 2+ It is ubiquitous in nature and is one of the essential trace elements for the human body. However, excessive intake can also lead to health problems, and severe cases can lead to Alzheimer's disease, Parkinson's disease, etc. 2+ It is also a commonly used metal, but it is highly toxic and very harmful to human health, such as causing damage to the liver, kidneys, gastrointestinal tract and nervous system. Heavy metal pollution of water sources is an important problem in environmental pollution. Moreover, due to Cu 2+ and Pb 2+ have been widely used and coexist in ecosystems, causing threats to human health and environmental unrest. Therefore, a selective and sensitive method was developed to simultaneously determine Cu 2+ and Pb 2+ It is of great significance.

[0003] Currently, there are many methods to detect Cu 2+ and Pb 2+ , such as atomic absorption spectroscopy (AAS), inductively coupled plasma atomic emission spectroscopy (ICP-OES) and inductively coupled plasma mass spectrometry (ICP-MS). However, these techniques usually require professional technicians or sophisticated equipment and are expensive, which limits their application. Therefore, it is necessary to develop simpler and cheaper methods to monitor Cu in the environment. 2+ and Pb 2+ Compared with these methods, electrochemical analysis methods have the advantages of low cost, simple operation, high sensitivity and low detection limit. Electrochemical sensors have attracted widespread attention in the detection of heavy metal ions in water. It is generally believed that direct electroreduction of Cu on traditional electrodes 2+ and Pb 2+ A high overpotential is required. In addition, the direct reduction of these two species on conventional electrodes has very similar potentials and is often significantly affected by fouling, which leads to overlapping voltammetric responses with relatively poor selectivity and reproducibility. Therefore, it is necessary to develop new electrode materials for the sensitive and selective simultaneous determination of Cu 2+ and Pb 2+ It has very superior appeal in the field of electrochemical analysis. Summary of the invention

[0004] The present invention utilizes the high specific surface area and electron mobility of GO and the excellent electron-donating performance of 5,10,15,20-tetrahydroxyphenyl-21H,23H-porphyrin (THPP) to synthesize a GO / THPP composite material with strong electron transfer ability and excellent electrochemical performance through π-π non-covalent interaction. In view of the synergistic effect between GO and THPP, the composite has good electrochemical performance. 2+ and Pb 2+ The present invention has demonstrated excellent electrocatalytic performance, based on which an electrochemical sensor with a wide linear range is constructed. Figure 1 ), successfully achieved the heavy metal ion Cu in sewage 2+ and Pb 2+ This new type of nanomaterial is expected to have great application potential in the field of environmental analysis due to its high sensitivity and selectivity for simultaneous detection.

[0005] The invention provides a non-metallic porphyrin / graphene oxide nanocomposite. The non-metallic porphyrin is non-covalently assembled to GO through π-π interaction. The non-metallic porphyrin is 5,10,15,20-tetrahydroxyphenyl-21H,23H-porphyrin (THPP).

[0006] The invention also provides a method for preparing the nanocomposite, which comprises mixing an aqueous solution of graphene oxide with an ethanol solution of non-metallic porphyrin, and then centrifuging, washing and freeze-drying the mixture.

[0007] Preferably, the concentration of the graphene oxide aqueous solution is 0.1-5 mg mL -1 The concentration of non-metal porphyrin ethanol solution is 0.1-5 mg mL -1 , the mixing ratio of the two is 1-5:1.

[0008] The present invention further provides a method for simultaneously detecting Cu 2+ and Pb 2+ An electrochemical sensor comprising a glassy carbon electrode coated with the above-mentioned nanocomposite.

[0009] The present invention further provides a method for preparing an electrochemical sensor, characterized in that the preparation method comprises the following steps:

[0010] S1: The glassy carbon electrode was ground on sandpaper, then polished to a mirror surface on Al2O3, ultrasonically treated in water and ethanol, respectively, and dried with nitrogen;

[0011] S2: Prepare non-metal porphyrin / graphene oxide nanocomposites with a concentration of 0.5-2 mg mL -1 The GO / THPP suspension was prepared and coated on the S1 treated glassy carbon electrode.

[0012] Preferably, the glassy carbon electrode has a diameter of 3 mm and a geometric area of ​​0.07 cm 2 The coating is drop coating, and the amount of drop coating is 2-10 μL.

[0013] Preferably, the sandpaper is SiC sandpaper, and the polishing step requires polishing on 1.0 and 0.3 μm Al2O3 respectively.

[0014] Preferably, in step S1, ultrasonication is performed in water and ethanol for 1-5 min respectively.

[0015] The present invention finally provides an electrochemical sensor for simultaneously detecting Cu in water samples. 2+ and Pb 2+ Application in.

[0016] Preferably, the water sample contains K + 、Co 2+ NH4 + 、Na + Mg 2+ 、Al 3+ 、Zn 2+ , Ca 2+ 、SO4 2- 、NO3 - 、S2O8 2- , Cl- or more.

[0017] Compared with the prior art, the present invention has the following effects:

[0018] (1) The present invention modifies THPP on the surface of GO through π-π non-covalent bond interaction without destroying the sheet structure of GO. After the two are combined, the wrinkles on the surface of GO become relatively flat, and the layers overlap each other, greatly improving the conductivity and chemical stability of the composite material. The synergistic effect between GO and THPP accelerates the electron transfer between the redox probe and the electrode surface. Compared with other porphyrins, THPP has better synergy with GO, better effect, and is more suitable for application in electrochemical sensors.

[0019] (2) The detection limits of the electrochemical sensor prepared by the present invention for Cu2+ and Pb2+ are 1.5 μM and 1.6 μM respectively. + 、Co 2+ NH4 + 、Na + Mg 2+ 、Al 3+ 、Zn 2+ , Ca 2+ 、SO4 2- 、NO3 -、S2O8 2- , Cl - It has good anti-interference in water samples, and has the characteristics of wide detection range, good reproducibility and stability, and can successfully realize the residual Cu in actual water samples. 2+ and Pb 2+ simultaneous determination. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 : SEM images of (A) GO, (B) THPP, (C) and (D) GO / THPP;

[0021] Figure 2 : Ultraviolet-visible (UV-Vis) spectra of (A) GO, (B) THPP, (C) and (D) GO / THPP;

[0022] Figure 3 : FT-IR spectra of GO, THPP and GO / THPP (left: 4000-500cm -1 ); FT-IR spectra of GO, THPP and GO / THPP (right: 1000-950cm -1 );

[0023] Figure 4 :(A) Full XPS spectra of GO and GO / THPP nanocomposites; XPS spectra of C1s(B) and O1s(C) in GO; XPS spectra of C1s(D), O1s(E) and N1s(F) in GO / THPP nanocomposites;

[0024] Figure 5 :(A) Electrochemical impedance spectroscopy of Bare / GCE, GO / GCE, GO / THPP / GCE and (B) Electrochemical impedance spectroscopy of Bare / GCE and GO / THPP / GCE; (C) Bare / GCE, GO / GCE, GO / THPP / GCE containing 40 μM Cu in 0.1 M HAc-NaAc (pH = 5.0) 2+ and Pb 2+ Cyclic voltammogram; scan rate: 50mVs -1

[0025] Figure 6 :(A) GO / THPP / GCE containing 40μM Cu in 0.1MHAc-NaAc (pH=5.0) at different scan rates 2+ and Pb 2 + Cyclic voltammogram; scan rate: 10, 30, 50, 100, 150, 200, 250, 300 mVs -1 (B) and (C) Cu2+ and Pb 2+ The linear relationship between the redox peak current and the scan rate;

[0026] Figure 7 :(A) GO / THPP / GCE in 0.1MHAc-NaAc (pH=5.0) with different concentrations of Cu 2+ and Pb 2+ (ak, 5-900μM) DPVs. (B) and (C) Cu 2+ and Pb 2+ Linear calibration curve of current and concentration. DPV conditions: pulse amplitude = 50 mV; pulse width = 0.2 s;

[0027] Figure 8 :100μM Cu 2+ and Pb 2+ and other common cations and anions (Cu 2+ and Pb 2+ The interference study was performed on the 10-fold concentration of DETAILED DESCRIPTION

[0028] Example 1

[0029] Preparation of GO / THPP nanocomposites

[0030] The synthesis of the GO / THPP composite material prepared in this embodiment is mainly divided into three steps. First, a certain amount of GO is weighed and dissolved in deionized water to obtain a GO aqueous solution with a concentration of 1 mg mL-1 for standby use. Secondly, THPP is dissolved in an ethanol solution to prepare a solution with a concentration of 1 mg mL-1, and the two are mixed in a ratio of 2:1 and ultrasonicated for 2 hours. Finally, a dark green GO / THPP nanocomposite material is obtained after centrifugation, washing, and freeze-drying.

[0031] Example 2

[0032] Preparation of GO / THPP modified GCE (GO / THPP / GCE)

[0033] First, the glassy carbon electrode (GCE, d = 3 mm, geometric area 0.07 cm 2 ) were ground on SiC sandpaper and then polished to a mirror surface on 1.0 and 0.3 μm Al2O3, ultrasonicated in water and ethanol for 2 min, respectively, and dried with nitrogen. Finally, 5 μL of 1 mg mL -1 The GO / THPP suspension was drop-coated on the polished electrode and dried at room temperature to obtain GO / THPP-modified GCE (GO / THP / GCE).

[0034] Comparative Example

[0035] This comparative example adopts the same method as Example 2, except that GO suspension is used to replace the GO / THPP suspension in Example 2 to prepare the GO modified electrode.

[0036] Example 3

[0037] The GO / THPP nanocomposite material prepared in Example 1 was characterized.

[0038] Its SEM characterization is as follows Figure 1 As shown by Figure 1 From the A region, we can see that GO has a multi-layered sheet structure. Figure 1 It can be seen from area B that the morphology of THPP is a nano-stacked block structure, and they overlap and stack together to form large block aggregates. Figure 1 The C and D regions of the graph show the microscopic morphology of the GO / THPP nanocomposite. THPP is modified on the GO surface through π-π non-covalent bond interactions, without destroying the GO sheet structure. After the two are combined, the wrinkles on the GO surface become relatively flat, and the layers overlap each other, which will greatly improve the conductivity and chemical stability of the composite material.

[0039] UV-Vis spectroscopy characterization of composite materials Figure 2 As shown in the figure, the UV-Vis absorption spectrum of GO in ethanol solution has no obvious absorption peak, and the UV-Vis absorption spectrum of THPP in ethanol shows a strong Soret band at 418nm, and 4 weak Q bands between 500 and 700nm, at 517nm, 554nm, 593nm and 650nm respectively. Compared with the UV-Vis absorption spectra of GO / THPP and THPP, the Soret band absorption peak of GO / THPP nanocomposite is at 420nm, which only slightly red-shifts (~2nm), and the positions of the 4 weak Q band absorption peaks have basically not changed, indicating that the π-π non-covalent interaction forms a J-type aggregate with GO as the core. The results show that after GO and THPP react to form a complex, the geometric structure of THPP does not change, and GO and THPP interact through π-π non-covalent bonds.

[0040] Figure 3 The GO, THPP, and GO / THPP are shown at 4000-500 cm -1 and 1000-950cm -1The Fourier transform infrared (FT-IR) spectrum of GO / THPP showed similar spectral characteristics to THPP, indicating that GO had no significant effect on the structure of THPP and that the GO / THPP nanocomposite was successfully synthesized through π-π non-covalent bond interactions. Figure 4 The full spectrum analysis experimental results of XPS further showed that there was neither the formation of new bonds nor the breaking of old bonds in the GO / THPP nanocomposite material, and the two synthesized the GO / THPP nanocomposite material through π-π non-covalent bond interaction.

[0041] Example 4

[0042] The GO / THPP modified GCE prepared in Example 2 and Comparative Example 2 were characterized.

[0043] Figure 5 Regions A and B show the [Fe(CN)6] 3- / [Fe(CN)6] 4- As a probe of electrochemical activity, Nyquist plots of different electrodes (frequency 10 -2 -10 5 Hz). Figure 5 As shown in the B area, in a 0.1M KCl solution containing 5mM K3[Fe(CN)6] / K4[Fe(CN)6], Bare / GCE showed an electron transfer impedance of about 250 ohm (red curve); after GO was modified on the electrode surface, the impedance increased significantly to about 1630 ohm (black curve), indicating that GO hindered the electron transfer between the redox probe and the electrode surface due to its poor conductivity. However, compared with GO / GCE, the impedance of GO / THPP / GCE was reduced to 167 ohm ( Figure 5 This further confirms that THPP is successfully assembled onto the surface of GO to form a GO / THPP nanocomposite, thereby promoting electron transfer between the redox probe and the electrode surface.

[0044] Figure 5 Region C shows the 2+ and Pb 2+ CV graphs of Bare / GCE, GO / GCE and GO / THPP / GCE in 0.1MHAc-NaAc (pH=5.0) solution. The CV curves of Bare / GCE and GO / GCE have a Pb near -0.48V. 2+ / Pb reduction peak, there is a Cu near 0V 2+ / Cu reduction peak, Cu 2+ and Pb 2+The potential difference between the reduction peaks is 480 mV. The CV graph of GO / THPP / GCE also shows two obvious reduction peaks due to Cu 2+ +2e - →Cu, Cu appears at 0.11V 2+ The reduction peak of Pb 2+ +2e - →Pb, Pb appears at -0.44V 2+ The reduction peak of Cu 2+ and Pb 2+ The peak current intensity of GO / THPP / GCE is significantly enhanced, and there is a more obvious peak potential difference (550mV) between the two, which indicates that GO / THPP / GCE has a strong affinity for Cu 2+ and Pb 2+ It has more excellent electrocatalytic activity and high sensitivity, and can realize the simultaneous detection of two ions.

[0045] Figure 6 Region A shows the GO / THPP / GCE in 0.1M HAc-NaAc (pH = 5.0) buffer solution containing 40 μM Cu at different scanning speeds. 2+ and Pb 2+ We studied the CV graphs of different scan rates (10, 30, 50, 100, 150, 200, 250, 300 mVs -1 ) for Cu 2+ and Pb 2+ Effect of Cu on the electrochemical performance of GO / THPP / GCE. 2+ and Pb 2+ The redox peak current intensity increases with the increase of scanning rate. Figure 6 As shown in the B and C regions, Cu 2+ and Pb 2+ The peak current intensity is linearly related to the scan rate half, which indicates that Cu 2+ and Pb 2+ The redox reaction on the GO / THPP electrode surface is a quasi-reversible surface-controlled electrochemical process.

[0046] Figure 7 Region A is the GO / THPP / GCE in the presence of different concentrations of Cu 2+ and Pb 2+ DPV diagram of 0.1MHAc-NaAc (pH=5.0) solution. 2+ The reduction peak current at -0.06 V increases with the increase of its concentration, and the response current is similar to that of Cu 2+ The concentration of Figure 7B), the linear range is 5-300μM and 300-900μM, and the linear regression equations are: Cu 2+ =-0.01128C Cu 2+ -0.89966(R 2 =0.958),I Cu 2+ =-0.00303C Cu 2+ -3.3759, (R 2 =0.993), the detection limit was 1.5μM; Pb 2+ The reduction peak current at -0.52 V increases with the Pb 2+ The response current increases with the increase of Pb concentration. 2+ The concentration of Pb 2+ ( Figure 7 The linear ranges are 5-250 μM and 250-900 μM, and the linear regression equations are: Pb 2+ =-0.01682C Pb 2+ -1.58312(R 2 =0.969),I Pb 2+ =-0.00445C Pb 2+ -4.58159(R 2 =0.998), and the detection limit was 1.6 μM. Compared with the reported literature, GO / THPP / GCE in this study was more effective in the simultaneous detection of Cu 2+ and Pb 2 + It has a wider concentration range and higher detection sensitivity.

[0047] In addition, we also studied other interferences from common coexisting substances in real water samples, such as adding 10 times Cu 2+ and Pb 2+ The concentration of cations and anions (K + 、Co 2+ NH4 + 、Na + Mg 2+ 、Al 3+ 、Zn 2+ , Ca 2+ 、SO4 2- 、NO3 - 、S2O8 2- , Cl - ), and its test results are for Cu 2+and Pb 2+ The current response has no effect ( Figure 8 ). The results show that GO / THPP / GCE is effective for simultaneous detection of Cu 2+ and Pb 2+ It has good selectivity. At the same time, we also studied the reproducibility and stability of the GO / THPP composite modified electrode. The Cu 2+ and Pb 2+ The current response in 0.1MHAc-NaAc (pH=5.0) buffer solution was used to analyze the reproducibility of GO / THPP / GCE. The results showed that Cu 2+ and Pb 2+ The peak current responses of the sensors were basically consistent, demonstrating that the sensor had good reproducibility. To further confirm the long-term stability of GO / THPP / GCE, GO / THPP / GCE was stored at room temperature for one week and then tested in 0.2 mM Cu in 0.1 M HAc-NaAc (pH = 5.0) two weeks later. 2+ and Pb 2+ The results showed that GO / THPP / GCE was responsive to Cu after being stored at room temperature for two weeks. 2+ and Pb 2+ The current response is basically consistent with the initial value, which proves that the sensor has good stability.

[0048] To further evaluate the practicality of the proposed sensor, we conducted experiments on residual Cu in tap water (surface water, Huai'an, China), river water (Sun Dahong River, Huai'an, China), and factory wastewater (secondary wastewater treatment plant, Huai'an, China). 2+ and Pb 2+ The actual water sample was filtered through a 0.45 μm microporous membrane to eliminate micron-sized impurities, and then diluted to 10 times with 0.1 M HAc-NaAc (pH = 5.0) buffer. Table 1 shows the concentration of Cu 2+ andPb 2+ Test results in real water samples (n=3), in which different standard concentrations of Cu 2+ and Pb 2+ (100, 150, 200 μM), the recoveries ranged from 97.84% to 103.85%, and the relative standard deviations (RSDs) were all less than 5%, which showed acceptable accuracy and further suggested that the GO / THPP composite can be effectively applied to the detection of Cu in real samples. 2+ and Pb 2+ simultaneous determination.

[0049] Table 1. Cu 2+ and Pb 2+Test results in actual water samples (n=3)

[0050]

[0051] a The average value of three determinations;

[0052] b Recovery rate = detected value / added amount × 100%.

Claims

1. A method for simultaneous detection of Cu 2+ and Pb 2+ An electrochemical sensor, characterized in that The electrochemical sensor comprises a glassy carbon electrode, which is coated with a non-metallic porphyrin / graphene oxide nanocomposite; in the nanocomposite, the non-metallic porphyrin is non-covalently assembled to graphene oxide GO through π-π interaction, and the non-metallic porphyrin is THPP; the preparation method of the nanocomposite comprises the following steps: mixing a graphene oxide aqueous solution with an ethanol solution of the non-metallic porphyrin, centrifuging, washing, and freeze-drying; the concentration of the graphene oxide aqueous solution is 0.1-5 mg mL -1 The concentration of the non-metal porphyrin ethanol solution is 0.1-5 mg mL -1 , the mixing ratio of the two is 1-5:

1.

2. A method for preparing an electrochemical sensor as claimed in claim 1, characterized in that , the preparation method comprises the following steps: S1: The glassy carbon electrode was ground on sandpaper, then polished to a mirror surface on Al2O3, ultrasonically treated in water and ethanol, respectively, and dried with nitrogen; S2: Prepare non-metal porphyrin / graphene oxide nanocomposites with a concentration of 0.5-2 mg mL -1 The GO / THPP suspension was prepared and coated on the S1 treated glassy carbon electrode.

3. The preparation method according to claim 2, characterized in that The glassy carbon electrode has a diameter of 3 mm and a geometric area of ​​0.07 cm 2 The coating is drop coating, and the amount of drop coating is 2-10 μL.

4. The preparation method according to claim 2, characterized in that , the sandpaper is SiC sandpaper, and the polishing step requires polishing on 1.0 and 0.3 μm Al2O3 respectively.

5. The preparation method according to claim 2, characterized in that , in step S1, ultrasonication was performed in water and ethanol for 1-5 min respectively.

6. An electrochemical sensor as claimed in claim 1 for simultaneously detecting Cu in water samples 2+ and Pb 2+ Application in.

7. The use according to claim 6, characterized in that , the water sample contains K + 、Co 2+ NH4 + 、Na + Mg 2+ 、Al 3 + 、Zn 2+ , Ca 2+ 、SO4 2- 、NO3 - 、S2O8 2- , Cl - One or more of .